Open learner models and pedagogical strategies in higher education: a meta-synthesis of approaches to self-regulated learning - Robles Mucho, Jonathan L.; Andrade-Girón, Daniel C.; Benites-Tirado, Violeta R.; Quispe-Maquera, Nelly Beatriz; Ayala-Jara, Carmen; Tito Chura, Hugo Euler; Luna-Victoria, Flor Marlene; Laura-De La Cruz, Kevin Mario; Rivera-Lozada, Oriana; Cerna Salcedo, Alberto Antonio; Jaramillo Arica, Pedro Segundo; Barboza, Joshuan J. (Frontiers in Education, 2026)
Open Learner Models (OLMs) are increasingly positioned as pedagogical tools capable of enhancing self-regulated learning (SRL) within higher education. Despite considerable technological progress, the pedagogical mechanisms through which OLMs support students' regulatory behaviors, metacognitive processes and motivational engagement remain insufficiently theorized. This review synthesizes empirical studies exploring OLMs that intentionally integrate pedagogical strategies in order to deepen understanding of how these models influence SRL across its preparatory, performance and reflective phases. Drawing on thematic meta-synthesis of 26 studies, the review identifies a continuum of OLMs—Inspectable, Negotiable, Editable, and Persuasive/Adaptive—that reflects progressively greater levels of learner agency, transparency, and co-regulation. Across this continuum, the pedagogical design of OLMs emerges as a critical determinant of their educational value: inspectable models predominantly support monitoring and awareness; negotiable models foster active calibration and dialogic feedback; editable models strengthen autonomy and goal-setting; and adaptive models, frequently mediated by artificial intelligence, offer personalized scaffolding that sustains engagement and reflection. Together, these findings illuminate how pedagogically enriched OLMs can operate as metacognitive mediators rather than purely analytical systems, enabling students to interpret feedback, make informed learning decisions and assume increasing ownership of their learning trajectories. The review offers a theoretically grounded framework that informs the design of transparent, ethical, and learner-centered OLMs, with implications for instructional practice, digital pedagogy, and the broader field of educational research.Systematic review registrationCRD420251237223.